Strategi Guru Penggerak dalam Menumbuhkan Karakter Moderat pada Peserta Didik Melalui Literasi di Madrasah - Dicky Artanto; Muqowim; Rr. Ayu Dewi Widowati (STAI Terpadu Yogyakarta, 2022)
This study aims to determine the role and strategy of the moderator driving teacher (GPM) in growing moderate values ​​in students with a literacy approach. The object of the research is the Moderation Motivator Mr. Dwi Atmaja who is also a teacher at MTsN 3 Surabaya. This study applies the field research method, which uses data and documents collected from the field. Meanwhile, data analysis uses Miles and Huberman, namely by collecting data, reducing data, presenting data, and drawing conclusions or verifying data. The results of the study show that moderate attitudes can be started to be cultivated through learning and literacy. Students are taught to use social media properly and wisely and are trained in the habit of accessing news information from trusted sources.